Incidence, Timing, and Possible Risk Factors for Post-Cesarean Wound Infection among Low-Risk Patients in Zaria, Nigeria: A Cross-Sectional Study - Zubairu, Usman; Abdul, Muhammad; Bawa, Umma; Madugu, Nana; Ghazzali, Sakina (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: Rising cesarean section rates worldwide have led to an increase in post-operative complications, especially wound infection, and endometritis. Low-risk cesarean sections are still at risk of these infections despite the absence of common risk factors. The burden and possible risk factors for these have not been widely documented in patients without major risk factors.Aim: To determine the incidence, timing of diagnosis, and possible risk factors for wound infection in low-risk cesarean sections.Settings and Design: A prospective cross-sectional study conducted among consenting women undergoing low-risk cesarean sections, defined as the absence of established risk factors for post-operative wound infection.Materials and Methods: Participants' sociodemographic and obstetric characteristics were documented in a structured proforma. The primary outcome measure was the incidence and timing of wound infection. Secondary outcome measures were the incidences of endometritis and febrile morbidity. The data were analyzed using SPSS version 21 and Windows WINPEPI.Results: The incidence of wound infection was 11.2% (19); endometritis—20.6% (35); febrile morbidity—4.1% (7). The mean timing of diagnosis of wound infection and endometritis were 10.22 ± 3.64 and 11.57 ± 3.34 days, respectively. Grandmultiparity (P= 0.007), low maternal educational levels (P= 0.014), endometritis (p =